1999
DOI: 10.1046/j.1525-1314.1999.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrology of gedrite‐bearing rocks in mid‐crustal ductile shear zones from the Eastern Ghats Belt, India

Abstract: A suite of metapelitic, basic and quartzofeldspathic rocks intruded by enderbitic gneiss from the southernmost tip of the Eastern Ghats Belt, India, and metamorphosed at c. 750–800 °C, 6 kbar, were subjected to repeated ductile shear deformation, hydration, cooling and accompanying alkali metasomatism along narrow shear zones. Gedrite‐bearing assemblages developed in the shear zones traversing metapelitic rocks. Interpretation of the reaction textures in an appropriate P–T  grid in the system FMASH, an isother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…As the Napier samples are from the vicinity of shear zones, Harley (1985) concluded that the gedrite is a product during later shearing. Dasgupta et al (1999) reported gedrite with up to 2.6 wt.% Na 2 O in sheared rocks from the Eastern Ghats Belt (India). Since the Paramati rocks are also located within the northern domain of the Palghat Cauvery Shear System, we do not rule out a similar possibility of gedrite formation during a retrograde event during shearing.…”
Section: Discussionmentioning
confidence: 99%
“…As the Napier samples are from the vicinity of shear zones, Harley (1985) concluded that the gedrite is a product during later shearing. Dasgupta et al (1999) reported gedrite with up to 2.6 wt.% Na 2 O in sheared rocks from the Eastern Ghats Belt (India). Since the Paramati rocks are also located within the northern domain of the Palghat Cauvery Shear System, we do not rule out a similar possibility of gedrite formation during a retrograde event during shearing.…”
Section: Discussionmentioning
confidence: 99%
“…5). The presence of orthoamphiboles suggests an early retrogression due to shearing in granulite grade conditions (Dasgupta et al, 1999). Clinopyroxene to hornblende transformation indicates a thermal drop to 750-775°C at a pressure of 4-8 kbar (Spear, 1981).…”
Section: P-t Conditions Of Amphibolite Faciesmentioning
confidence: 99%
“…As the rocks are collected from the vicinity of shear zones, Harley (1985) discussed that the gedrite is a product of later shearing. Dasgupta et al (1999) also reported gedrite with up to 2.6 wt% Na 2 O in sheared rocks from the Eastern Ghats Belt, India. Although a metasomatic origin through the activity of fluids along shear zones is a possible mechanism to explain the occurrence of sodicgedrite in our samples, halogen analyses of the gedrites demon-* Number of oxygens.…”
Section: Discussionmentioning
confidence: 86%
“…The mineral has also been reported in several Mg Al rich rocks from ultrahigh temperature (UHT) metamorphic terranes (e.g., Harley, 1985;Ouzegane et al, 1996;Dasgupta et al, 1999). Such gedrite in UHT rocks generally contain high Na 2 O (Na A > 0.5) as sodicgedrite (Leake et al, 1997).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation